Copy number variation analysis implicates novel pathways in patients with oculo‐auriculo‐vertebral‐spectrum and congenital heart defects. Issue 3 (24th May 2021) - Guida, Valentina; Sparascio, Francesca Piceci; Bernardini, Laura; Pancheri, Francesco; Melis, Daniela; Cocciadiferro, Dario; Pagnoni, Mario; Puzzo, Marianna; Goldoni, Marina; Barone, Chiara; Hozhabri, Hossein; Putotto, Carolina; et al.
Abstract: Oculo‐auriculo‐vertebral spectrum (OAVS) is a developmental disorder of craniofacial morphogenesis. Its etiology is unclear, but assumed to be complex and heterogeneous, with contribution of both genetic and environmental factors. We assessed the occurrence of copy number variants (CNVs) in a cohort of 19 unrelated OAVS individuals with congenital heart defect. Chromosomal microarray analysis identified pathogenic CNVs in 2/19 (10.5%) individuals, and CNVs classified as variants of uncertain significance in 7/19 (36.9%) individuals. Remarkably, two subjects had small intragenic CNVs involving DACH1 and DACH2, two paralogs coding for key components of the PAX‐SIX‐EYA‐DACH network, a transcriptional regulatory pathway controlling developmental processes relevant to OAVS and causally associated with syndromes characterized by craniofacial involvement. Moreover, a third patient showed a large duplication encompassing DMBX1 / OTX3, encoding a transcriptional repressor of OTX2, another transcription factor functionally connected to the DACH‐EYA‐PAX network. Among the other relevant CNVs, a deletion encompassing HSD17B6, a gene connected with the retinoic acid signaling pathway, whose dysregulation has been implicated in craniofacial malformations, was also identified. Our findings suggest that CNVs affecting gene dosage likely contribute to the genetic heterogeneity of OAVS, and implicate the PAX‐SIX‐EYA‐DACH network as novel pathway involved in the etiology of this developmental trait. Abstract :